Brain Reward System And Its Volumetric Investigations In Alcohol Addiction - Tabara, M. F.; Atmaca, M.; Yildirim, H.; Solmaz, O.; Essibayi, M. A. (Cambridge Univ Press, 2023)
[Abstract Not Available]
31st European Congress of Psychiatry -- MAR 25-28, 2023 -- Paris, FRANCE